Efficacy and safety of genotype-guided warfarin dosing versus non-genotype-guided warfarin dosing strategies: A systematic review and meta-analysis of 27 randomized controlled trials. Issue 210 (February 2022) - Wang, Xinrui; Tang, Borui; Zhou, Meng; Liu, Lihong; Feng, Xin; Wang, Xin; Qiu, Kui
Abstract: Objective: To evaluate the efficacy and safety of genotype-guided dosing (GD) strategies compared to non−genotype−guided dosing (non-GD) strategies for warfarin. Methods: Databases were searched up to July 2021. Meta-analysis was conducted with the Review Manager software (version 5.4) and R (version 4.0.5). Risk ratio (RR), mean difference (MD), and 95% confidence intervals (CIs) were used. Subgroup analyses were conducted based on ethnicity and dosing regimen in non-GD group. Meta-regression was performed to evaluate the relation of covariates. This study is registered with PROSPERO (CRD42021245654). Results: 27 randomized controlled trials with a total of 9906 patients were included. The GD group resulted in a significantly improved time in therapeutic range compared with non-GD group in follow-up duration within 30 days (MD: 5.95, 95%CI: 2.41–9.22, P  = 0.001) and beyond 30 days (MD: 4.93, 1.40–8.47, P  = 0.006), time to the first therapeutic international normalized ratio (MD: −1.80, −2.69 - −0.92, P  < 0.0001), and time to reach stable dose (MD: −5.08, −7.09 - −3.07, P  < 0.00001), incidence of major bleeding events (RR: 0.50, 0.33–0.75, P  = 0.0008), total bleeding events (RR: 0.83, 0.73–0.95, P  = 0.006), and thromboembolism (RR: 0.69, 0.49–0.96, P  = 0.03). No differences were found in stable dose achievement, minor bleeding events, over anticoagulation, and all-cause mortality. Four improved efficacy outcomes were observed in GD group compared with fixed dosing group. Only time to the therapeutic INR was shortened in GD group compared with clinical adjusted dosing group. The result showed no difference of safety outcomes between GD group and fixed dosing group whereas a decreased incidence of major bleeding events was observed when comparing to clinical adjusted dosing group. Conclusion: GD strategy was superior to fixed dosing strategy in term of efficacy outcomes and comparable to fixed dosing strategy in safety outcomes. Clinical adjusted regimen could partly substitute the genotype-guided dosing strategy for efficacy in insufficient conditions, but the risk of major bleeding events should be monitored. Highlights: The initial dosage of warfarin is hard to ascertain so it takes lots of time to achieve the target INR. Previous RCTs showed inconsistent results of the efficacy and safety of genotype-guided warfarin dosing strategy. Genotype-guided dosing strategy was superior in efficacy outcomes and comparable in safety outcomes compared with fixed dosing strategy. Clinical adjusted regimen could partly substitute the genotype-guided dosing strategy for efficacy in insufficient conditions.